Comparison of reverse-transcriptase polymerase chain reaction (RT-PCR) and rapid test for the detection of bovine rotavirus and bovine coronavirus in anatolian water buffaloes - Bulut, Oya; Uyunmaz Saklı, Gülşah; Hasöksüz, Mustafa; Dik, Irmak; Hadimli, Hasan Hüseyin; Hitit, Mustafa (Selçuk University Press, 2020)
Aim: Coronaviruses and Rotaviruses are important virologic factors for both animal and human health in Turkey and the world Bovine Rotavirus (BRV) and Bovine Coronavirus (BCoV) in cattle cause significant economic losses The aim of this study was to determine the presence of BRV and BCoV in Anatolian buffaloes which were on the same farms with cattle For this purpose, presence of these two viruses were investigated by Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) and BRV-BCoV Rapid tests and sensitivity and specificity ratios of these two tests were compared Materials and Methods: In this study, 230 Anatolian buffaloes were clinically evaluated in cattle farms in Afyonkarahisar region Fecal samples were collected from 27 buffaloes which had clinical signs (weakness, dehydration, vomiting, watery consistency and yellow stool) The fecal samples were evaluated by Rapid Test and RT-PCR for Bovine Rotavirus and Bovine Coronavirus The analyzes were performed according to the procedure of the commercial RT-PCR and rapid kits
Keywords: BCoV; Rapid test; Bovine coronavirus; RT-PCR; Anatolian water buffaloes; BRV; Anadolu mandas; Bovine rotavirus; Hızlı test; 2. Zero hunger; 3. Good health